Bernhard Kahn - Jacobowsky, C. (Nordisk judaistik/Scandinavian Jewish Studies, 1979)
In this article, the author presents Bernhard Kahn (1876–1955) born in Oskarshamn, Sweden. During his career he grew an extensive international network, which made him one of the most known Swedish Jews abroad of the 20th century. Towards the end of 1904, Kahn was employed as secretary-general of Hilfsverein der Deutschen Juden which had been founded in 1901 and commenced its full activity in 1903, after the progrom in Kishinev. As secretary general of HV, Kahn worked hard to give constructive assistance to the Jews in Eastern Europe, among other things. Later he worked in Berlin as European director of the Joint. Kahn perceived that his position as JDC’s European director was untenable as long as he remained in Berlin. His connections with the hated American Jewish community were unpopular in Berlin. In the end of March 1933 he prepared his departure and moved his office to Paris. In 1938, during Kahn’s last active year in Europe before he moved to the United States, there were 687 loan societies with 191,000 members, small businessmen, farmers and craftsmen. JDC’s Reconstruction Foundation, with Kahn as its executive director, was not only active among the Jews in Poland, but also in Belgium, Estonia, Finland, Greece, Latvia, Lithuania, Romania, Czechoslovakia and Turkey.